2011
DOI: 10.2528/pierl11041601
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Balanced Quadruple Subharmonical Mixer With a Compact if Extraction

Abstract: A novel 21-35 GHz single-balanced quadruple subharmonic monolithic passive mixer is fabricated using the 0.15 µm GaAs pHEMT process. This mixer consists of a local oscillation (LO) spiral balun and a radio frequency (RF) band pass filter which has an intermediate frequency (IF) extracted feature utilizing a pair of anti-parallel Schottky barrier diode to achieve quadruple subharmonic mixing mechanism. The RF band pass filter formed with an interdigital coupler and a low-pass network is used to reduce the chip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The balun consists of two offset broadside coupled spiral transformers. Contrary to most other reported miniature spiral type Marchand balun designs, e.g., [11][12][13][14][15][16][17], our design adds five shunt capacitors externally to the spiral transformer structures. The lumped element equivalent circuit model of the spiral type Marchand balun configured as a symmetrical four port network is shown in Fig.…”
Section: Balun Optimizationmentioning
confidence: 96%
“…The balun consists of two offset broadside coupled spiral transformers. Contrary to most other reported miniature spiral type Marchand balun designs, e.g., [11][12][13][14][15][16][17], our design adds five shunt capacitors externally to the spiral transformer structures. The lumped element equivalent circuit model of the spiral type Marchand balun configured as a symmetrical four port network is shown in Fig.…”
Section: Balun Optimizationmentioning
confidence: 96%
“…Another advantage is that the wide frequency gap between the RF and LO signals simplifies the LO and RF separation. Frequency mixer circuits, either in microstrip [11][12][13] or in monolithic technology [14][15][16][17][18], generally use transistors [19][20][21][22][23][24], or diodes [25][26][27][28], in order to generate the desired nonlinear behavior.…”
Section: Introductionmentioning
confidence: 99%
“…As in any amplifier [8][9][10], mixer [11][12][13][14][15][16][17], or active antenna with mixing capabilities [18], noise behavior [11,12] and IF signal distortion [13,18] are key factors that must be rigorously analyzed and minimized. In this work, it will be shown that the figures of merit which are traditionally used to analyze the linearity of conventional mixers cannot be directly applied to an autonomous circuit like the HSOM, because of the influence of the input RF signal power on the parameters of the self-oscillating signal.…”
Section: Introductionmentioning
confidence: 99%